Newborn English Bulldogs with Multiple Malformation Syndrome and Lethal Characters - Si-Jung Jang; Minkyung Kim; Hyeon-Jeong Lee; Young-Sung You; Jaehoon Lee; Sung-Lim Lee (The Korean Society of Animal Reproduction and Biotechnology, 2019)
A female English bulldog was gave birth two neonates by cesarean section on the sixty one days after mating, but both neonates were died soon after birth. The bodies of neonates were diagnosed using radiography, ultrasonography, computed tomography and necropsy immediately after death. Both neonates had caudal regression syndrome, butterfly vertebra, hydrocephalus, umbilical hernia, cleft palate and bow-legged hind-limb. At necropsy, neonates had mild fetal anasarca, cleft lip and the skull was remained non-union. At thoracic cavity, only three ribs and thoracic spines were existed and patent ductus arteriosus was found. At abnormal cavity, the renal ectopia was found with abnormal morphology. In the present case, those English bulldog neonates with multiple congenital malformation syndromes seriously suffered vertebral column anomalies and that may induced by neural tube defects in during embryonic period. To prevent congenital malformation occurring in English bulldog, further in depth studies are needed for the breed specific genetic diversity and for the reason of behind genetic abnormality in these breed.